Ferroaluminate cement-based concrete pavement patching material as well as preparation method and application thereof

By adding specific additives to the iron aluminate cement-based concrete pavement repair materials, the hydration reaction and mineral powder hydration are promoted, and a high-density structure is formed, which solves the wear resistance, carbonization resistance and low bonding strength of traditional repair materials. The problem has significantly improved the strength and life of the repair material.

CN119285312AActive Publication Date: 2025-01-10UNIV OF JINAN

Patent Information

Application Number
CN202411836740.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-01-10
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Traditional sulfur aluminate cement-based concrete pavement repair materials have poor wear resistance, poor carbonization resistance and low bonding strength, which leads to a significantly reduced service life of the repair material and insufficient binding force with the old interface, which can easily lead to the fall of the repair material.

Method used

Using iron aluminate cement-based concrete pavement repair materials, adding triisopropanolamine or diethanol monoisopropanolamine to promote ore phase dissolution, forming a complex to accelerate hydration reaction, and combining calcium formate and sulfate to promote ore powder Hydration improves structural density, and generates iron-containing calcium vanadium through the reaction of calcium sulfosilicate and vaterite, enhancing strength and bonding properties.

Benefits of technology

It significantly improves the early and full-age strength of the repair material, improves the freezing resistance, enhances the bonding force with the old concrete interface, extends the service life of the repair material, and prevents falling off.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285312A_ABST
    Figure CN119285312A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based pavement patching materials, and particularly discloses an aluminoferrite cement-based concrete pavement patching material as well as a preparation method and application thereof. The repairing material is prepared from the following raw material components in parts by weight: 25 to 45 parts of iron aluminate cement clinker, 2 to 5 parts of Portland cement clinker, 5 to 15 parts of composite gypsum, 2 to 4 parts of calcium sulphosilicate, 2 to 4 parts of vaterite, 10 to 25 parts of mineral powder, 40 to 50 parts of fine aggregate, 0.05 to 0.25 part of triisopropanolamine or diethanolisopropanolamine, 0.75 to 1.5 parts of calcium formate and 0.5 to 1.0 part of sulfate. The strength of the repairing material can be improved in the whole age, the freeze-thaw resistance is improved, and the repairing material has good bonding strength with the pavement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based pavement repair materials, and in particular to a ferroaluminate cement-based concrete pavement repair material and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the continuous development of my country's transportation industry, a large number of roads have been built in my country, and the area of ​​cement concrete pavement has also been increasing. Due to changes in the environment and climate and the impact of automobile loads, cement concrete pavements are prone to problems such as polishing, peeling, and cracking, which seriously affect the appearance of the road and transportation. Therefore, it is very necessary to repair cement concrete pavements.

[0004] Traditional sulphoaluminate cement-based concrete pavement repair materials have problems such as poor wear resistance, poor carbonization resistance, and low bonding strength, which significantly reduce the service life of concrete pavement repair materials. Although ferroaluminate cement-based pavement repair materials can solve the above problems, the increase in the solid solubility of Fe2O3 in ferroaluminate cement in calcium sulphoaluminate and calcium ferroaluminate mineral phases leads to a decrease in mineral hydration activity and hydration degree, which in turn causes the early, middle and late strength of this repair material to be low, and the antifreeze performance is reduced. In addition, the above-mentioned repair material also has insufficient bonding strength with the old interface of the repaired part, which easily causes the repair material to fall off during service, resulting in repair failure. Summary of the invention

[0005] In view of the above problems, the present invention provides a ferroaluminate cement-based concrete pavement repair material and a preparation method and application thereof, which can improve the strength of the repair material at all ages, improve the poor freeze-thaw resistance, and have good bonding strength with the old interface of the repaired part, thereby increasing the service life of the repaired part. Specifically, the technical solution of the present invention is as follows.

[0006] Firstly, the invention discloses an aluminoaluminate cement-based concrete pavement repair material, wherein the raw materials thereof include the following components: 25-45 parts by weight of aluminoaluminate cement clinker, 2-5 parts by weight of silicate cement clinker, 5-15 parts by weight of composite gypsum, 2-4 parts by weight of calcium sulfosilicate, 2-4 parts by weight of vaterite, 10-25 parts by weight of mineral powder, 40-50 parts by weight of fine aggregate, 0.05-0.25 parts by weight of triisopropanolamine or diethanol monoisopropanolamine, 0.75-1.5 parts by weight of calcium formate, and 0.5-1.0 parts by weight of sulfate.

[0007] Furthermore, the raw materials also include 15 to 31 parts by weight of mixing water.

[0008] Furthermore, the sulfate includes at least one of sodium sulfate, potassium sulfate, aluminum sulfate, barium sulfate and the like.

[0009] Furthermore, the composite gypsum is formed by mixing dihydrate gypsum and anhydrite. Optionally, the mass ratio of the dihydrate gypsum to the anhydrite is 5-7:3-5.

[0010] Further, the mineral powder is graded from powders of 400-500 mesh, 500-600 mesh, 600-700 mesh, and 700-800 mesh. Optionally, the mass ratios of the powders of 400-500 mesh, 500-600 mesh, 600-700 mesh, and 700-800 mesh are 45-55:20-25:15-20:5-10, respectively.

[0011] Furthermore, the calcium ferroaluminate sulfide (C4A 3-x F x $) The solid solution content x of iron in is: 0.4≤x≤0.9.

[0012] Furthermore, the calcium aluminoferrite (C2A 1-y F y ) The solid solution content y of iron in it is: 0.5≤y≤0.7.

[0013] Furthermore, the fine aggregate includes at least one of river sand, machine-made sand, quartz sand, etc.

[0014] Secondly, the present invention discloses a preparation method of the ferroaluminate cement-based concrete pavement repair material, comprising the following steps: mixing the ferroaluminate cement clinker, silicate cement clinker, composite gypsum, calcium sulfosilicate, vaterite, mineral powder, fine aggregate, triisopropanolamine or diethanol monoisopropanolamine, calcium formate, and sulfate, stirring evenly, and then adding the mixing water and stirring evenly to obtain the repair material.

[0015] Finally, the invention discloses the application of the alumina-ferrocement-based concrete pavement repair material in construction engineering, road engineering or bridge engineering.

[0016] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: (1) Triisopropanolamine or diethanol monoisopropanolamine is added to the repair material of the present invention, which can effectively promote the dissolution of the mineral phase in the ferroaluminate cement clinker and react with the Fe in calcium ferroaluminate and calcium ferroaluminate. 3+The formation of complex accelerates the dissolution of the composite gypsum, thereby accelerating the hydration of ferroaluminate cement clinker and significantly enhancing the early strength of the repair material. At the same time, the disordered migration of the complex in the liquid phase increases the internal activation energy, making the hydration reaction easier to proceed, thereby promoting the generation of hydration products, making their distribution more uniform, and making the system more compact. 3+ The tetrahedron formed after complexation replaced part of the Q in the CSH gel b 2 Si tetrahedron forms C-(F)-SH gel, which makes the structure of the repair material denser, thereby improving the mechanical strength of the repair material over the entire age.

[0017] (2) The formate ions released by calcium formate can penetrate the hydration product (CSH gel layer) covering the surface of C2S grains in ordinary Portland cement clinker, accelerating the dissolution of C2S. However, since the ferroaluminate cement clinker generates C-(F)-SH gel, and the tetrahedrons generated by complexation replace part of the Q b 2 Si tetrahedron makes C-(F)-SH gel more active and the formate ion penetration resistance becomes extremely small, which greatly accelerates the hydration of C2S and the speed of generating CSH gel, making the structure of the repair material more compact and enhancing the early and late strength of the repair material.

[0018] (3) The calcium formate and sulfate in the repair material of the present invention can synergistically promote the hydration of the mineral powder. This is because the sulfate dissolves in the hydration liquid phase to make SO4 2- The content increases, promoting the hydration process and consuming Ca 2+ , accelerate the dissolution of mineral powder to provide Ca 2+ At this time, calcium formate accelerates the Ca 2+ Ca(OH)2 and CSH gel are formed, which in turn causes the mineral powder to rapidly hydrate and generate a large amount of CSH gel, thereby reducing the porosity of the repair material, making the structure denser, and significantly reducing the entry of carbon dioxide in the air and external moisture, thereby improving the anti-carbonization and anti-freeze properties of the repair material.

[0019] (4) The triisopropanolamine or diethanol monoisopropanolamine and calcium formate in the repair material of the present invention can synergistically dissolve the old concrete surface of the concrete pavement repair site to a certain extent, because calcium formate penetrates the hydration product layer on the old concrete surface, allowing triisopropanolamine or diethanol monoisopropanolamine to contact and wrap the unhydrated silicate minerals to dissolve them again. This helps the repair material penetrate into the old concrete and then undergo a hydration reaction to form a gelling product, thereby promoting the bonding between the new and old interfaces, enhancing the bonding performance between the repair material and the concrete pavement, and preventing problems such as cracking at the interface causing the repair material to fall off.

[0020] (5) The calcium sulfosilicate and vaterite in the repair material of the present invention can react with Al(OH)3 and Fe(OH)3 generated by the hydration of the ferroaluminate cement clinker to generate iron-containing calcium vanadium, which further provides strength. This is because the vaterite can quickly dissolve to provide Ca 2+ To promote the dissolution of calcium sulfosilicate, calcium sulfosilicate dissolves to produce Ca 2+ 、SO4 2- and SiO4 4- The Al(OH)3 and Fe(OH)3 generated by the hydration of the ferroaluminate cement clinker react with the above-mentioned ions to produce iron-containing calcium vanadium, so that these ions in the hydration liquid phase are in an unsaturated state, thereby increasing the dissolution driving force of C5S2$, accelerating the hydration of C5S2$ to generate iron-containing calcium vanadium and CSH gel, and further improving the strength of the repair material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0022] Figure 1 This is a sample of the ferroaluminate cement-based concrete pavement repair material prepared in the following Example 1.

[0023] Figure 2 This is a 28d compressive strength test chart of the repair material prepared in the following Example 1.

[0024] Figure 3 The following is a graph showing the bonding strength of the repaired specimen of Example 1. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0026] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions.

[0027] In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments.

[0028] Example 1 A method for preparing a ferroaluminate cement-based concrete pavement repair material comprises the following steps: (1) Weigh the raw materials according to the following proportions: 25 parts by weight of ferroaluminate cement clinker, 2 parts by weight of 42.5 ordinary Portland cement clinker, 5 parts by weight of composite gypsum with a fineness of 200 mesh, 2 parts by weight of calcium sulfosilicate powder with a fineness of 300 mesh, 2 parts by weight of vaterite powder with a fineness of 300 mesh, 10 parts by weight of mineral powder, 44 parts by weight of river sand fine aggregate, 0.05 parts by weight of triisopropanolamine, 1.3 parts by weight of calcium formate, and 0.5 parts by weight of sodium sulfate. Among them, the calcium sulfoaluminate in the ferroaluminate cement clinker is C4A 2.5 F 0.5 $、Calcium aluminoferrite is C2A 0.4 F 0.6 The composite gypsum is mixed with dihydrate gypsum and anhydrite in a mass ratio of 6:4, the fine aggregate is medium sand, and the mineral powder is mixed with 50 parts by weight of 400-mesh mineral powder, 25 parts by weight of 500-mesh mineral powder, 15 parts by weight of 600-mesh mineral powder, and 10 parts by weight of 700-mesh mineral powder.

[0029] (2) Add the raw materials in step (1) into a blender and stir for 3 minutes, then add the resulting powder (such as Figure 1 15 parts by weight of mixing water was added to the mixture and stirred for 2 minutes to obtain a repair material.

[0030] Performance test: (1) According to GBT 17671-2021, the 2h compressive strength and 28d compressive strength (such as Figure 2 (2) The old concrete substrate is placed in a mold, and then the repair material prepared in this embodiment is poured into the gap of the mold. Then, the bonding strength of the repaired specimen is tested according to GBT 17671-2021 (as shown in FIG. Figure 3(as shown) to measure the bonding performance between the repair material and the old concrete. (3) The wear resistance of the repair material prepared in this embodiment is tested according to T0567-2005 "Test method for wear resistance of cement concrete". (4) The antifreeze performance (strength loss after 100 freeze-thaw cycles) of the repair material prepared in this embodiment is tested according to "GB∕T 50082-2009". The test results of the above performance indicators are shown in the following table: .

[0031] Example 2 A method for preparing a ferroaluminate cement-based concrete pavement repair material comprises the following steps: (1) Weigh the raw materials according to the following proportions: 32 parts by weight of ferroaluminate cement clinker, 3 parts by weight of 42.5 ordinary Portland cement clinker, 10 parts by weight of composite gypsum with a fineness of 200 mesh, 4 parts by weight of calcium sulfosilicate powder with a fineness of 300 mesh, 4 parts by weight of vaterite powder with a fineness of 300 mesh, 17 parts by weight of mineral powder, 40 parts by weight of river sand fine aggregate, 0.25 parts by weight of triisopropanolamine, 1.5 parts by weight of calcium formate, and 0.5 parts by weight of potassium sulfate. Among them, the calcium sulfoaluminate in the ferroaluminate cement clinker is C4A 2.6 F 0.4 $、Calcium aluminoferrite is C2A 0.5 F 0.5 The composite gypsum is mixed with dihydrate gypsum and anhydrite in a mass ratio of 5:5, the fine aggregate is medium sand, and the mineral powder is mixed with 55 parts by weight of 400-mesh mineral powder, 23 parts by weight of 500-mesh mineral powder, 20 parts by weight of 600-mesh mineral powder, and 10 parts by weight of 700-mesh mineral powder.

[0032] (2) Add the raw materials of step (1) into a mixer and stir for 3 minutes. Then, add 25 parts by weight of mixing water to the obtained powder and stir for 2 minutes to obtain a repair material.

[0033] Performance test: The same method as in Example 1 was used to test the 2h compressive strength, 28d compressive strength, bonding strength with old concrete, wear resistance, and frost resistance of the repair material prepared in this example. The test results of the above performance indicators are shown in the following table: .

[0034] Example 3 A method for preparing a ferroaluminate cement-based concrete pavement repair material comprises the following steps: (1) Weigh the raw materials according to the following proportions: 45 parts by weight of ferroaluminate cement clinker, 5 parts by weight of 42.5 ordinary Portland cement clinker, 15 parts by weight of composite gypsum with a fineness of 200 mesh, 3 parts by weight of calcium sulfosilicate powder with a fineness of 200 mesh, 3.5 parts by weight of vaterite powder with a fineness of 300 mesh, 25 parts by weight of mineral powder, 50 parts by weight of quartz sand fine aggregate, 0.25 parts by weight of diethanol monoisopropanolamine, 0.75 parts by weight of calcium formate, and 1.0 parts by weight of barium sulfate. Among them, the calcium sulfoaluminate in the ferroaluminate cement clinker is C4A 2.1 F 0.9 $、Calcium aluminoferrite is C2A 0.7 F 0.7 The composite gypsum is mixed with dihydrate gypsum and anhydrite in a mass ratio of 7:3, the fine aggregate is medium sand, and the mineral powder is mixed with 45 parts by weight of 500-mesh mineral powder, 20 parts by weight of 600-mesh mineral powder, 18 parts by weight of 700-mesh mineral powder, and 5 parts by weight of 800-mesh mineral powder.

[0035] (2) Add the raw materials of step (1) into a mixer and stir for 3 minutes. Then, add 31 parts by weight of mixing water to the obtained powder and stir for 2 minutes to obtain a repair material.

[0036] Performance test: The same method as in Example 1 was used to test the 2h compressive strength, 28d compressive strength, bonding strength with old concrete, wear resistance, and frost resistance of the repair material prepared in this example. The test results of the above performance indicators are shown in the following table: .

[0037] Example 4 A method for preparing a ferroaluminate cement-based concrete pavement repair material comprises the following steps: (1) Weigh the raw materials according to the following proportions: 25 parts by weight of ferroaluminate cement clinker, 2 parts by weight of 42.5 ordinary Portland cement clinker, 5 parts by weight of composite gypsum with a fineness of 200 mesh, 2 parts by weight of calcium sulfosilicate powder with a fineness of 300 mesh, 2 parts by weight of vaterite powder with a fineness of 300 mesh, 10 parts by weight of mineral powder, 44 parts by weight of river sand fine aggregate, 1.3 parts by weight of calcium formate, and 0.5 parts by weight of sodium sulfate. Among them, the calcium sulfoaluminate in the ferroaluminate cement clinker is C4A 2.5 F 0.5 $、Calcium aluminoferrite is C2A 0.4 F 0.6 The composite gypsum is mixed with dihydrate gypsum and anhydrite in a mass ratio of 6:4, the fine aggregate is medium sand, and the mineral powder is mixed with 50 parts by weight of 400-mesh mineral powder, 25 parts by weight of 500-mesh mineral powder, 15 parts by weight of 600-mesh mineral powder, and 10 parts by weight of 700-mesh mineral powder.

[0038] (2) Add the raw materials of step (1) into a mixer and stir for 3 minutes. Then, add 15 parts by weight of mixing water to the obtained powder and stir for 2 minutes to obtain a repair material.

[0039] Performance test: The same method as in Example 1 was used to test the 2h compressive strength, 28d compressive strength, bonding strength with old concrete, wear resistance, and frost resistance of the repair material prepared in this example. The test results of the above performance indicators are shown in the following table: .

[0040] Example 5 A method for preparing a ferroaluminate cement-based concrete pavement repair material comprises the following steps: (1) Weigh the raw materials according to the following proportions: 32 parts by weight of ferroaluminate cement clinker, 3 parts by weight of 42.5 ordinary Portland cement clinker, 10 parts by weight of composite gypsum with a fineness of 200 mesh, 4 parts by weight of calcium sulfosilicate powder with a fineness of 300 mesh, 4 parts by weight of vaterite powder with a fineness of 300 mesh, 17 parts by weight of mineral powder, 40 parts by weight of river sand fine aggregate, and 0.25 parts by weight of triisopropanolamine. 2.6 F 0.4 $、Calcium aluminoferrite is C2A 0.5 F 0.5 The composite gypsum is mixed with dihydrate gypsum and anhydrite in a mass ratio of 5:5, the fine aggregate is medium sand, and the mineral powder is mixed with 55 parts by weight of 400-mesh mineral powder, 23 parts by weight of 500-mesh mineral powder, 20 parts by weight of 600-mesh mineral powder, and 10 parts by weight of 700-mesh mineral powder.

[0041] (2) Add the raw materials of step (1) into a mixer and stir for 3 minutes. Then, add 25 parts by weight of mixing water to the obtained powder and stir for 2 minutes to obtain a repair material.

[0042] Performance test: The same method as in Example 1 was used to test the 2h compressive strength, 28d compressive strength, bonding strength with old concrete, wear resistance, and frost resistance of the repair material prepared in this example. The test results of the above performance indicators are shown in the following table: .

[0043] Example 6 A method for preparing a ferroaluminate cement-based concrete pavement repair material comprises the following steps: (1) Weigh the raw materials according to the following proportions: 45 parts by weight of ferroaluminate cement clinker, 5 parts by weight of 42.5 ordinary Portland cement clinker, 15 parts by weight of composite gypsum with a fineness of 200 mesh, 3 parts by weight of calcium sulfosilicate powder with a fineness of 200 mesh, 3.5 parts by weight of vaterite powder with a fineness of 300 mesh, 25 parts by weight of mineral powder, 50 parts by weight of quartz sand fine aggregate, and 1.0 part by weight of barium sulfate. Among them, the calcium sulfoaluminate in the ferroaluminate cement clinker is C4A 2.1 F 0.9 $、Calcium aluminoferrite is C2A 0.7 F 0.7 The composite gypsum is mixed with dihydrate gypsum and anhydrite in a mass ratio of 7:3, the fine aggregate is medium sand, and the mineral powder is mixed with 45 parts by weight of 500-mesh mineral powder, 20 parts by weight of 600-mesh mineral powder, 18 parts by weight of 700-mesh mineral powder, and 5 parts by weight of 800-mesh mineral powder.

[0044] (2) Add the raw materials of step (1) into a mixer and stir for 3 minutes. Then, add 31 parts by weight of mixing water to the obtained powder and stir for 2 minutes to obtain a repair material.

[0045] Performance test: The same method as in Example 1 was used to test the 2h compressive strength, 28d compressive strength, bonding strength with old concrete, wear resistance, and frost resistance of the repair material prepared in this example. The test results of the above performance indicators are shown in the following table: .

[0046] Example 7 A method for preparing a ferroaluminate cement-based concrete pavement repair material comprises the following steps: (1) Weigh the raw materials according to the following proportions: 32 parts by weight of ferroaluminate cement clinker, 3 parts by weight of 42.5 ordinary Portland cement clinker, 10 parts by weight of dihydrate gypsum with a fineness of 200 mesh, 4 parts by weight of calcium sulfosilicate powder with a fineness of 300 mesh, 4 parts by weight of vaterite powder with a fineness of 300 mesh, 17 parts by weight of mineral powder, 40 parts by weight of river sand fine aggregate, 0.25 parts by weight of triisopropanolamine, 1.5 parts by weight of calcium formate, and 0.5 parts by weight of potassium sulfate. Among them, the calcium sulfoaluminate in the ferroaluminate cement clinker is C4A 2.6 F 0.4 $、Calcium aluminoferrite is C2A 0.5 F 0.5 The fine aggregate is medium sand, and the mineral powder is a mixture of 55 parts by weight of 400-mesh mineral powder, 23 parts by weight of 500-mesh mineral powder, 20 parts by weight of 600-mesh mineral powder, and 10 parts by weight of 700-mesh mineral powder.

[0047] (2) Add the raw materials of step (1) into a mixer and stir for 3 minutes. Then, add 25 parts by weight of mixing water to the obtained powder and stir for 2 minutes to obtain a repair material.

[0048] Performance test: The same method as in Example 1 was used to test the 2h compressive strength, 28d compressive strength, bonding strength with old concrete, wear resistance, and frost resistance (strength loss after 100 freeze-thaw cycles) of the repair material prepared in this example. The test results of the above performance indicators are shown in the following table: .

[0049] Example 8 A method for preparing a ferroaluminate cement-based concrete pavement repair material comprises the following steps: (1) Weigh the raw materials according to the following proportions: 45 parts by weight of ferroaluminate cement clinker, 5 parts by weight of 42.5 ordinary Portland cement clinker, 15 parts by weight of composite gypsum with a fineness of 200 mesh, 25 parts by weight of mineral powder, 50 parts by weight of quartz sand fine aggregate, 0.25 parts by weight of diethanol monoisopropanolamine, 0.75 parts by weight of calcium formate, and 1.0 parts by weight of barium sulfate. Among them, the calcium ferroaluminate in the ferroaluminate cement clinker is C4A 2.1 F 0.9 $、Calcium aluminoferrite is C2A 0.7 F 0.7 The composite gypsum is mixed with dihydrate gypsum and anhydrite in a mass ratio of 7:3, the fine aggregate is medium sand, and the mineral powder is mixed with 45 parts by weight of 500-mesh mineral powder, 20 parts by weight of 600-mesh mineral powder, 18 parts by weight of 700-mesh mineral powder, and 5 parts by weight of 800-mesh mineral powder.

[0050] (2) Add the raw materials of step (1) into a mixer and stir for 3 minutes. Then, add 31 parts by weight of mixing water to the obtained powder and stir for 2 minutes to obtain a repair material.

[0051] Performance test: The same method as in Example 1 was used to test the 2h compressive strength, 28d compressive strength, bonding strength with old concrete, wear resistance, and frost resistance of the repair material prepared in this example. The test results of the above performance indicators are shown in the following table: .

[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A ferroaluminate cement-based concrete pavement repair material, characterized in that: The raw materials of the repair material include the following components: 25-45 parts by weight of ferroaluminate cement clinker, 2-5 parts by weight of silicate cement clinker, 5-15 parts by weight of composite gypsum, 2-4 parts by weight of calcium sulfosilicate, 2-4 parts by weight of vaterite, 10-25 parts by weight of mineral powder, 40-50 parts by weight of fine aggregate, 0.05-0.25 parts by weight of triisopropanolamine or diethanol monoisopropanolamine, 0.75-1.5 parts by weight of calcium formate, and 0.5-1.0 parts by weight of sulfate.

2. The ferroaluminate cement-based concrete pavement repair material according to claim 1, characterized in that: The raw materials also include 15 to 31 parts by weight of mixing water.

3. The ferroaluminate cement-based concrete pavement repair material according to claim 1, characterized in that: The sulfate includes at least one of sodium sulfate, potassium sulfate, aluminum sulfate and barium sulfate.

4. The ferroaluminate cement-based concrete pavement repair material according to claim 1, characterized in that: The composite gypsum is mixed with dihydrate gypsum and anhydrite; the mass ratio of the dihydrate gypsum to the anhydrite is 5-7:3-5.

5. The ferroaluminate cement-based concrete pavement repair material according to claim 1, characterized in that: The mineral powder is graded from powders with finenesses of 400-500 mesh, 500-600 mesh, 600-700 mesh, and 700-800 mesh; the mass ratios of the powders with finenesses of 400-500 mesh, 500-600 mesh, 600-700 mesh, and 700-800 mesh are 45-55:20-25:15-20:5-10, respectively.

6. The ferroaluminate cement-based concrete pavement repair material according to claim 1, characterized in that: The C4A of the ferroaluminate cement 3-x F x $The solid solution content x of iron in the medium is: 0.4≤x≤0.

9.

7. The ferroaluminate cement-based concrete pavement repair material according to claim 1, characterized in that: The C2A of the ferroaluminate cement 1-y F y The solid solution content y of iron in China is: 0.5≤y≤0.

7.

8. The ferroaluminate cement-based concrete pavement repair material according to any one of claims 1 to 7, characterized in that: The fine aggregate includes at least one of river sand, machine-made sand and quartz sand.

9. The method for preparing the alumina-ferrocement-based concrete pavement repair material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing the ferroaluminate cement clinker, silicate cement clinker, composite gypsum, calcium sulfosilicate, vaterite, mineral powder, fine aggregate, triisopropanolamine or diethanol monoisopropanolamine, calcium formate and sulfate, stirring evenly, then adding mixing water and stirring evenly to obtain the repair material.

10. Use of the ferroaluminate cement-based concrete pavement repair material according to any one of claims 1 to 7 in construction engineering, road engineering or bridge engineering.

Citation Information

Patent Citations

  • Cement mortar dry type mixture for rapidly repairing cement road surface

    CN109809772A

  • Cement pavement thin-layer repairing material and using method thereof

    CN111704421A

  • Concrete road rapid repairing master batch and concrete road repairing material

    CN112321241A

  • Polymer sulphoaluminate cement repair mortar as well as preparation method and application thereof

    CN116444237A

  • Excellent salt stress and frost stress and chemically resistant concrete repair materials, and method for repairing concrete structure using this same

    KR101764895B1

Cited By

  • Calcium aluminoferrite-calcium sulphosilicate cement-based expanding agent as well as preparation method and application thereof

    CN119528470A

  • A calcium aluminoferrite-calcium sulfosilicate cement-based expansion agent and its preparation method and application

    CN119528470B